ECONOMIC IMPACT OF BIRDS' ATTACKS ON SUNFLOWER CROPS - CASE STUDY - Otilia COTUNA; Veronica SĂRĂȚEANU; Mirela PARASCHIVU; Ion DUMITRESCU; George Doru LAIEȘ; Ramona ȘTEF (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The economic impact of birds on sunflower crops is less studied in Romania and worldwide. In the present study, three sunflower crops established near Timisoara were analysed. The aim of the study was to highlight the economic losses produced by birds during the emergence of seedlings or immediately after sowing as well as before harvesting. The hybrids cultivated were NK Neoma and SY Futura AR. Yield damage was estimated both after emerging and before harvest. Bird flocks were visually assessed by direct field observations during feeding. The birds species identified were Columba livia livia and Corvus frugilegus. Economic losses were calculated considering all technological elements. Damage was 100% in the plot A521 (2.5 ha) and 90% in the plot A519 (6.5 ha). The plot A136 (14.84 ha) was not attacked by birds. The expenses were 3,826.7 lei/ha in 2024. The yields were 0 kg (plot A521), 277 kg (plot A519) and 2670 kg (plot A136). Profit was achieved on plot A136 in the amount of 1,342.3 lei. The selling price for sunflower seeds was 1.8 lei/kg in 2024.